Identification and characterization of the peptides with calcium‐binding capacity from tilapia (Oreochromis niloticus) skin gelatin enzymatic hydrolysates - Bingtong, Liu; Yongliang, Zhuang; Liping, Sun (Journal of food science, 2020)
The aim of this study was to isolate and identify the peptides with calcium‐binding capacity from the different tilapia skin gelatin enzymatic hydrolysates. The complex protease was selected and its hydrolysates were further separated using gel filtration chromatography (Sephadex G‐25) and reverse phase high‐performance liquid chromatography. Two purified peptides with strong calcium‐binding capacity were identified as Tyr‐Gly‐Thr‐Gly‐Leu (YGTGL, 509.25 Da) and Leu‐Val‐Phe‐Leu (LVFL, 490.32 Da). The calcium‐binding capacities of YGTGL and LVFL reached 76.03 and 79.50 µg/mg, respectively. The structures of the complex of purified peptides and calcium (YGTGL‐Ca and LVFL‐Ca) were characterized by ultraviolet‐visible spectroscopy (UV‐VIS), scanning electron microscopy (SEM), X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and mass spectrometry (LC‐MS/MS). The results of UV‐VIS, SEM, and XRD indicated that YGTGL‐Ca and LVFL‐Ca were formed as new compounds. The results of FTIR and LC‐MS/MS indicated the nitrogen atom of the amino group and the oxygen atom of the carboxyl group in terminates of the peptides provided primary binding sites. Moreover, the hydrophobic amino acids in purified peptides could provide more chelating spaces. This study was of great significance for the development of calcium supplement foods. Practical Application Compared with inorganic calcium and organic calcium, the bioactive gelatin peptide chelated calcium has the characteristics of high utilization rate, high solubility, and high absorption rate. The raw materials are extracted from the tilapia processed waste, which reduce the cost, make full use of resources, and improve the bioavailability. The tilapia skin gelatin peptide calcium chelate can be directly absorbed by the human body, and the absorption efficiency is high, further improving the resource utilization rate and having high economic benefits, which is a comprehensive supplement that can also be used as a functional food.